Both Acute and Consecutive Days of Formoterol Stimulation Influence Myogenic, Mitochondrial, and myomiR Gene Expression in Human Skeletal Muscle Cells - Ryan A. Gordon; Emily L. Zumbro; Gena D. Guerin; Matthew L. Sokoloski; Vic Ben-Ezra; Christopher S. Brower; Rhett B. Rigby; Anthony A. Duplanty (Muscles, 2023)
Skeletal muscle physiology is regulated by microRNA that are localized within skeletal muscle (myomiRs). This study investigated how the expression of myomiRs and genes regulating skeletal muscle mass and myogenesis are influenced in response to acute and consecutive days of exercise-related signaling using the exercise mimetic, formoterol, in vitro. Human skeletal muscle cells were proliferated and differentiated for 6 days. Experimental conditions included: (a) control, (b) acute formoterol stimulation (AFS), and (c) consecutive days of formoterol stimulation (CFS). For AFS, myotubes were treated with 30 nM of formoterol for three hours on day 6 of differentiation, and this was immediately followed by RNA extraction. For CFS, myotubes were treated with 30 nM of formoterol for three hours on two or three consecutive days, with RNA extracted immediately following the final three-hour formoterol treatment. We observed increased myomiR expression for both AFS and CFS. AFS appeared to promote myogenesis, but this effect was lost with CFS. Additionally, we observed increased expression of genes involved in metabolism, mitochondrial biogenesis, and muscle protein degradation in response to AFS. myomiR and gene expression appear to be sensitive to acute and long-term exercise-related stimuli, and this likely contributes to the regulation of skeletal muscle mass.